(untitled) (Modern American Journal of Social Sciences and Humanities, 2025)
Among various types of forensic linguistic examinations, authorship attribution holds a special place. Determining the author of a text requires a detailed and methodical investigation. Identifying both general and specific linguistic features, analyzing relevant sources, and forming an objective conclusion ensure the reliability of the expert’s judgment. This article explores the distinctive features, methodological criteria, and significance of author identification within linguistic expertology.